To cut or not to cut – that is the question: a comparative analysis of long-term follow-up after complete and incomplete electroconization of the cervix due to high-grade squamous intraepithelial lesion - Suchońska, Barbara E.; Gajewska, Małgorzata E.; Blok, Joanna M. (Frontiers in Oncology, 2024)
Electroconization of the uterine cervix (LEEP/LLETZ) is an appropriate and sufficient procedure for high-grade squamous epithelial lesion – HSIL. Negative margins are considered fundamental for confirming the absence of residual disease. Further management after incomplete excision among women who have not completed their procreative plans is difficult because subsequent cervical procedures may cause issues with carrying a pregnancy to term. Since almost one-third of the untreated patients with HSIL will develop cervical carcinoma, it is essential to balance the desire to radicalize treatment with its obstetric consequences. We compared the further clinical course of the patients after complete and incomplete procedures to observe whether completeness of excision is necessary for a successful outcome. We aim to identify risk factors that influence persistent or recurrent HSIL. The study has comprised 781 patients aged 18-85 – the research group was composed of 140 (17.93%) patients after incomplete conization and the control group of 641 (82.17%) patients after the complete one. Patients were scheduled for follow-up examinations every 6 months – including cytology, HPV typing, and colposcopy with tissue sampling. The Chi-square test or Fisher's exact test was performed as a tool for group comparisons for variables on the qualitative scale. Univariable and multivariable logistic regression models have been used to determine factors associated with the risk of persistent or recurrent HSIL. To evaluate the discriminatory ability of the logistic regression models, the Area Under the Curve (AUC) was calculated. The statistical analysis results don’t indicate a statistical significance between the frequency of HSIL in groups. HPV infection has increased the risk of persistent/recurrent lesions by 38 times, constituting the most important factor. Close follow-up instead of inconsiderate repeat procedures should be taken under consideration among patients of reproductive age after incomplete conization of the cervix. HPV typing may be an essential method to predict recurrent cervical dysplasia. Promoting HPV typing and vaccination can reduce the number of invasive procedures and improve quality of life and obstetrics outcomes.